Design and fabrication of micro-coils for NMR micro probes - Zishan Ali Syed Mohammed (2018)
The miniaturization of probes for Magnetic Resonance (MR) analytical methods-Nuclear Magnetic Resonance (NMR), Magnetic Resonance Imaging (MRI), or relaxometry- has been the latest trend which allows portability and analysis of the chemical composition of minute (in the range of nL to L) volumes of sample. MR analyses typically require that such a probe is used in an external setup with a very strong constant magnetic field with no temporal variation and external detector circuits. A critical aspect of the success of such an experiment is to ensure a high signal-to-noise ratio (SNR). However, the resulting value of the SNR delivered by a miniature probe has a complicated dependence on both the external measurement setup, the chemical composition of the sample and the probe design. For probe designers, there are no clear guidelines to suggest how a given the probe will behave under any external measurement setup or chemical composition of the sample under test, or how to approach a probe design so as to optimize design parameters for a good performance in terms of SNR in an MR analysis, e.g. an NMR experiment.